2011
DOI: 10.1097/sla.0b013e31820d9b04
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Lesser-Impact-Factor Surgical Journals As a Source of Negative and Inconclusive Outcomes Reporting

Abstract: Quality rather than outcome should be the measure on which a publication decision is made; commercial bias may further complicate this balance. Lower IF-rated journals may serve a decidedly useful purpose by publishing more negative and inconclusive outcome studies. The practice of focusing disproportionately on the positive outcomes of most studies may result in unbalanced evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…This would allow editors and reviewers to assess adequacy of prepublication trial registration. In addition to improving the accuracy of data in trial protocols submitted to trial registries and papers, 26,27 investigators should be required to enter a minimum dataset before trial protocol admission to the registry is granted. Also in published RCTs, a direct link to the trial protocol in the relevant registry should be provided in the HTML text of all papers as this will facilitate reader assessment of possible selective reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow editors and reviewers to assess adequacy of prepublication trial registration. In addition to improving the accuracy of data in trial protocols submitted to trial registries and papers, 26,27 investigators should be required to enter a minimum dataset before trial protocol admission to the registry is granted. Also in published RCTs, a direct link to the trial protocol in the relevant registry should be provided in the HTML text of all papers as this will facilitate reader assessment of possible selective reporting bias.…”
Section: Discussionmentioning
confidence: 99%
“…Impact factor of journals is a two-edged sword, e.g. regarding its correlation with the true scientific or practical impact of let's say radiation technology or neurosurgery advances, and the publication bias that strikes negative or inconclusive studies [6][7][8][9][10]. Article download rates might provide some indication for visibility and impact, but will depend on presence and quantity of fees charged by the publisher.…”
mentioning
confidence: 99%
“…although this correlates with the believe that the impact factor is a surrogate of the publication quality, there is some concern related to a positive results bias: trials with negative results are less likely to be accepted at high impact factor journals. 22 Declared funding might relate to the type of institutions involved: large academic center or studies funded by national agencies require the funding grant number to be reported in their articles, and these studies would probably have larger funds and resources than smaller trials.…”
Section: Discussionmentioning
confidence: 99%